Why concern regarding privacy differs: The influence of age and (non-)participation on Facebook - Wouter M. P. Steijn; Alexander P. Schouten; Anton H. Vedder (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2016)
Young people have obtained a reputation for caring less about their privacy due to their self-revealing presence on social media. Although one might easily be inclined to think that young people do not care about their privacy, an explanation for this could be that young people simply have a different idea of what privacy entails. This study aims to investigate the underlying mechanisms that may explain differences in privacy concerns between younger and older people and between users and non-users of social network sites (SNSs). 1.008 users of SNS and 712 non-users participated in the study with a stratified distribution over adolescents, young adults, and adults. The results show that the difference in perceived risk-benefit balance partly mediates the relationship between use or non-use of SNSs and concern. SNS users are less concerned because they perceive more benefits relative to risks. Concern regarding privacy between young and old was mediated by their differences in privacy conceptions. Older individuals were more likely to associate situations related to personal information with privacy. In turn, these individuals reported more concern regarding their privacy.